Nothing Ventured, Nothing Gained: Parasite Infection is Associated with Entrepreneurial Initiation, Engagement, and Performance. (January 2021) - Lerner, Daniel A.; Alkærsig, Lars; Fitza, Markus A.; Lomberg, Carina; Johnson, Stefanie K.
There is growing evidence that human biology and behavior are influenced by infectious microorganisms. One such microorganism is the protozoan Toxoplasma gondii ( TG ). Using longitudinal data covering the female population of Denmark, we extend research on the relationship between TG infection and entrepreneurial activity and outcomes. Results indicate that TG infection is associated with a subsequent increase in the probability of becoming an entrepreneur, and is linked to other outcomes including venture performance. With parasite behavioral manipulation antithetical to rational judgment, we join a growing conversation on biology and alternative drivers of business venturing.